The last anniversary ebook - Moriarty, Liane (2010)
From Liane Moriarty, author of the #1 New York Times bestsellers Big Little Lies and Truly Madly Guilty, comes an unforgettable novel defined by her signature sharp wit, page-turning storyline, and lovable and eccentric characters. Sophie Honeywell always wondered if Thomas Gordon was the one who got away. He was the perfect boyfriend, but on the day he was going to propose, she broke his heart. A year later he married his travel agent, while Sophie has been mortifyingly single ever since. Now Thomas is back in her life because Sophie has unexpectedly inherited his aunt Connie's house on Scribbly Gum Island—home of the famously unsolved Munro Baby mystery. Sophie moves onto the island and begins a new life as part of an unconventional family, where it seems everyone has a secret. Grace, a beautiful young mother, is feverishly planning a shocking escape from her perfect life. Margie, a frumpy housewife, has made a pact with a stranger, while dreamy Aunt Rose wonders if maybe it's about time she started making her own decisions. As Sophie's life becomes increasingly complicated, she discovers that sometimes you have to stop waiting around—and come up with your own fairy-tale ending.